Fin-Tech UMKM untuk Stabilitas Sistem Keuangan Indonesia - Alfiatul Maulida (STIE Mandala Jember, 2020)
MSMEs contributed quite a large contribution to Indonesia's GDP (Gross Domestic Product) at 36.82%. When compared with the indicators in the assessment that support Indonesia's economic growth, this figure isvery large. In addition to this, as many as 98.7% of Indonesian businesses are Micro businesses. Thus, with this amount, MSMEs can absorb 89.17% of the domestic workforce according to the Deputy Chairperson of the National Economy and Industry Committee. In 2017, MSMEs that had been online as much as 7.7% and in 2019 targeted at 8% in the previous year, MSMEs had contributed significantly to Indonesia's economic growth. The nature of the research which is based on the philosophy of post positivity is used for the evaluation of natural tourist objects with researchers as a key instrument. Qualitative research is a method of data collection conducted by triangulation, data analysis is inductive, and the results of qualitative research emphasize the meaning ofgeneralization. Analysis results prove the use of Fintech MSME is very effective and efficient will be able to support the Indonesian Financial System with various indicators that support Indonesia's economic growth. Keyword: MSMEs, Financial Technology, Stabilization Financial System.